Crustal and Sedimentary Structures and Geodynamic Evolution of the West Antarctic Continental Margin and Pine Island Bay - Gohl, Karsten; Uenzelmann-Neben, G.; Eagles, Graeme; Fahl, A.; Feigl, Thomas; Grobys, J.; Just, Janna; Leinweber, Volker; Lensch, Norbert; Mayr, C.; Parsiegla, N.; Rackebrandt, Nick; et al. (2006)
Since the last glacial maximum the West Antarctic Ice Sheet (WAIS) with a base mostly beneath the present-day sea-level has experienced dramatic volume changes within short periods of time. Studies are urgently required to show how these short-term variations are related to volume changes in the older geological past. Next to the ice drainage basins of the Weddell Sea and the Ross Embayment, Pine Island Bay forms the third-largest outflow area for the West Antarctic ice-shield. The main ice streams from the WAIS into Pine Island Bay flow through the Pine Island and Thwaites Glacier systems, through which most of the glacial-marine sediments onto the shelf of Pine Island Bay and across the continental slope into the deep sea have been transported. Geophysical surveys of the sedimentary sequences and the underlying basement of the shelf and slope of the southern Amundsen Sea, Pine Island Bay and its adjacent continental rise would allow reconstructions of the formation of the tectonic and older sedimentary processes as well as to find out about the history of large-scale glaciation in West Antarctica. Accurate models of the geodynamic- tectonic evolution contain some of the most important parameters for understanding and reconstruction of the palaeo-environment. info:eu-repo/semantics/published